2017
DOI: 10.3892/ol.2017.7647
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EZH2 is associated with poor outcome in colorectal cancer

Abstract: Enhancer of zeste homolog 2 (EZH2), the critical component of polycomb group protein family, has been demonstrated to be overexpressed in various types of human cancer, including hepatocellular carcinoma, breast, bladder and lung cancer. The mechanism of how EZH2 promotes oncogenesis has also been well studied. However, little is known about the role of EZH2 in colorectal cancer (CRC). The main purpose of the present study was to analyze the association between EZH2 expression and the clinicopathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
(40 reference statements)
2
29
0
Order By: Relevance
“…DNA methylation in EZH2-binding regions positively correlated with cancer stage in 5 of 21 tested cancers, but trended negative in 3 cancer types (Additional file 2: Fig. S8), of which colon adenocarcinoma (COAD) had a significant negative correlation (p < 0.05, t approximation, Holm-Bonferroni correction), consistent with a previous report [35]. To further investigate the significance of the EZH2-binding regions, we used a Cox proportional hazards model to test for association between survival and average DNA methylation in these regions and found a significant association in 5 cancer types (Fig.…”
Section: Dna Methylation In Ezh2-binding Regions Is Associated With Csupporting
confidence: 89%
“…DNA methylation in EZH2-binding regions positively correlated with cancer stage in 5 of 21 tested cancers, but trended negative in 3 cancer types (Additional file 2: Fig. S8), of which colon adenocarcinoma (COAD) had a significant negative correlation (p < 0.05, t approximation, Holm-Bonferroni correction), consistent with a previous report [35]. To further investigate the significance of the EZH2-binding regions, we used a Cox proportional hazards model to test for association between survival and average DNA methylation in these regions and found a significant association in 5 cancer types (Fig.…”
Section: Dna Methylation In Ezh2-binding Regions Is Associated With Csupporting
confidence: 89%
“…Importantly, this study also found that EZH2 was an independent predictor of decreased overall survival in patients with colorectal cancer after multivariate analysis for lymph node and distant metastasis. These findings were supported by another study of 95 patients with colorectal cancer, in which high protein levels of EZH2 were associated with advanced clinical stage, histologic grade and independently predicted poor overall survival in this patient cohort [12]. Furthermore, Ohuchi et al showed that EZH2 protein expression levels gradually increased from normal colonic mucosa to dysplasia and colorectal cancer, suggesting an oncogenic role for EZH2 in the carcinogenesis process from benign mucosa to carcinoma [13].…”
Section: Colorectal Cancersupporting
confidence: 68%
“…EZH2 is increasingly expressed during the progression of hematopoietic and solid cancers (Bachmann et al, 2006;Chen et al, 2018;Karakashev et al, 2018;Patnaik et al, 2018;Sudo et al, 2005), and overexpression of mutant EZH2 has been recognized in a wide selection of B and T cell lymphoproliferative disorders (Morin et al, 2010;Raaphorst et al, 2000;Sasaki et al, 2011;Sneeringer et al, 2010;Visser et al, 2001). Therefore, considerable effort has been directed toward development of EZH2 inhibitors, but current specific EZH2 inhibitors can (B) GSEA for the NF-kB related genes in (A).…”
Section: Discussionmentioning
confidence: 99%